Backbone Conformations in Secondary and Tertiary Structural Units of Nucleic Acids. Constraint in the Phosphodiester Conformation - Yathindra, N. (1974)
The possible backbone phosphodiester conformations in a dinucleoside monophosphate and a dinucleoside triphosphate have been investigated by semiempirical energy calculations. Conformational energies have been computed as a function of the rotations ω′ and ω about the internucleotide P-O(3′) and P-O(5′) linkages, with the nucleotide residues themselves assumed to be in one of the preferred [C(3′)-endo] conformations. The terminal phosphates in a dinucleoside triphosphate greatly limit the possible conformations for the backbone (in a polynucleotide) compared to a dinucleoside monophosphate. There appear to be two major types of conformations that are favored for the backbone. The phosphodiester conformation (ω′,ω) ≃ (290°,290°) characteristic of helical structures is one of them, indicating that the polynucleotide backbone shows an inherent tendency for the helical conformation. The other favored conformation is centered at (ω′,ω) ≃ (190°,300°) and results in an extended backbone structure with unstacked bases. A third possible conformation centered at (ω′, ω) ≃ (200°, 60°) and the (190°, 300°) conformation appear to be important for the folding of a polynucleotide chain. The conformation (ω′,ω) ≃ (80°,80°), observed in a dinucleoside monophosphate and believed to be a candidate for producing an abrupt turn in a polynucleotide chain, is found to be stereochemically unfavorable in a dinucleoside triphosphate and a polynucleotide.